Peningkatan Hasil Belajar Pai Peserta Didik X TPL 1 Melalui Problem Based Learning (PBL) di SMK Negeri 2 Payakumbuh - Fadly Rijal (Jurnal Pendidikan Tuntas, 2024)
This study aims to improve Islamic Religious Education learning outcomes for class X TPL 1 students at SMK Negeri 2 Payakumbuh through the application of the Problem-Based Learning (PBL) model. This Classroom Action Research was conducted in two cycles, encompassing planning, implementation, observation, and reflection stages. The results showed a significant improvement in students' learning mastery, increasing from 20% in the pre-cycle stage to 74.2% in cycle I, and reaching 90.3% in cycle II. This success was attributed to the problem-based approach that actively engaged students in the learning process, the use of technology, and group discussions that enhanced critical thinking, collaboration, and problem-solving skills. The study demonstrates that the PBL model effectively improves student learning outcomes and aligns with the needs of 21st-century education.